A coletânea: um breve relato de uma graduação em música - Silva, Adelmo Henrique Fernandes da [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Este trabalho apresenta uma trajetória cronologia do início ate o final do cursos englobando as mostras de peças feitas durante o processo da graduação. Apresenta no texto analises, relatos, reflexões e acesso a paginas externas do catálogo criado com as obras para o Trabalho de Conclusão de Curso. Durante a apresentação os trechos musicais foram tocados para melhor referencia e complementação do trabalho de compilação das melhores peças escritas.

This work aims to present and analyze pieces created during undergraduate studies,organized chronologically, establishing a relationship between the development andimprovement of musical language writing skills, personal development as anindividual within the University, and the adversities presented during the years ofsocial isolation and the following years up to the present day. Throughout the text, theaccounts situate the moments of conception of the pieces, their purpose as anexercise, and finally, the musical analyses, which are illustrated. To carry out thiswork, it was necessary to compile the chosen works and publish the pieces on theweb, in the form of a website/catalog.
The collection: a short brief of a music undergraduate
Keywords: Composição (Música); Música - Análise, apreciação; Criação(Literária, artística, etc.); Estudantes universitários - Narrativas pessoais